Rare Case Of Accesory Cavitated Uterine Malformation - Sakhifa, A. Sithi; P. Bharathi, P. Bharathi; R. Jayanthi, R. Jayanthi; Kala, A. (Journal of Neonatal Surgery, 2025)
Accessory Cavitated Uterine Malformation (ACUM) is a rare and often underdiagnosed congenital uterine anomaly that typically presents in adolescents and young women with severe dysmenorrhea and pelvic pain. It is characterized by the presence of an accessory, non-communicating uterine cavity lined by functional endometrium within an otherwise normal uterus. ACUM is often mistaken for other Müllerian anomalies or gynecological pathologies such as hematometra, endometriosis, or fibroids due to overlapping clinical and radiological features. We report a rare case of a 16-year-old adolescent female who presented with severe cyclical lower abdominal pain since menarche, which was not relieved by medical management. Pelvic ultrasonography and MRI revealed a normal uterine anatomy with a well-circumscribed cystic lesion in the anterior wall of the uterus, suggestive of a cavitated lesion containing altered blood products. Diagnostic laparoscopy confirmed the presence of a non-communicating accessory cavity within the myometrium. Complete excision of the cavity and histopathological evaluation confirmed the diagnosis of ACUM. This case highlights the importance of considering ACUM as a differential diagnosis in young females presenting with intractable dysmenorrhea, especially when imaging shows a cystic lesion within a normal uterus. Early and accurate diagnosis is essential to relieve symptoms and prevent complications such as infertility or progression to chronic pelvic pain. Surgical excision remains the treatment of choice, offering complete symptom resolution and improved quality of life. Awareness of this rare condition among clinicians and radiologists is crucial to avoid unnecessary diagnostic delays and interventions